Optimization of cutting force via variable feed rate in dry turning lathe of AISI 304. (2022) - Agrawal, Riya; Kumar, Naveen; Parvez, Kausain; Srivastava, Ayush; Sarfaraz Alam, Md
Abstract: When we talk about metal cutting or metal removal process, turning operation is found to be the most favorable because of the ease with which it can be performed, also it is economical and gives significant results. But even though every industry focuses on optimization of turning process by increasing the metal removal rate and decreasing the power consumption by decreasing the cutting forces. This is achieved by setting up the optimum control factors which are decided by a series of experiments performed by adjusting input parameters like feed, cut depth, and cutting speed. This paper is focused on optimizing the cutting force by varying feed, cutting depth & cutting speed at various levels in AISI 304 SS turning with cemented-carbide insert as cutting tool. The experiment was developed on the basis of Taguchi's method of Design of Experiment which uses Taguchi's L9 Analysis of S/N ratio & Orthogonal Array Technique is done to get a plot for optimized control factors. Later ANOVA analysis is done to find out the relation between cutting force and control factor which demonstrates the contribution of each factor of control towards the cutting force.